2017
DOI: 10.1590/1678-4324-2017160174
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Microalgal Biomass grown in Anaerobic Sewage Treatment Effluent by the Coagulation-Flocculation Method: Effect of pH

Abstract: Harvesting is a critical step in microalgal biomass production process for many reasons. Among

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Mixotrophic cultivation is a generalized two-stage mode in which microalgae have a high initial content of organic carbon, but are induced for assotrophic assimilation of CO 2 due to depletion of organic substances and oxygen production through photosynthesis [ 35 , 36 ]. During mixotrophic cultivation, microalgae grow under optimal autotrophic and heterotrophic conditions, combining the advantages of both cultivation modes [ 37 ]. Under such conditions, acetyl-CoA is produced and maintained both by fixing CO 2 and extracellular organic carbon, which indicates a decrease in photoinhibition.…”
Section: Methods Of Microalgae Cultivationmentioning
confidence: 99%
“…Mixotrophic cultivation is a generalized two-stage mode in which microalgae have a high initial content of organic carbon, but are induced for assotrophic assimilation of CO 2 due to depletion of organic substances and oxygen production through photosynthesis [ 35 , 36 ]. During mixotrophic cultivation, microalgae grow under optimal autotrophic and heterotrophic conditions, combining the advantages of both cultivation modes [ 37 ]. Under such conditions, acetyl-CoA is produced and maintained both by fixing CO 2 and extracellular organic carbon, which indicates a decrease in photoinhibition.…”
Section: Methods Of Microalgae Cultivationmentioning
confidence: 99%
“…They found 93.3% of biomass recovery in 60 mg L −1 , smaller efficiency compared to results seen in this study at 60 mg L −1 (97.9%). In another study, Cassini et al [24] also found high efficiency (95.6%) using a tanninbased coagulant-flocculant (Tanfloc ® POP) for the harvest of microalgae biomass (Chlorella sp.) at 100 mg L −1 .…”
Section: Discussion Of Preliminary Treatmentsmentioning
confidence: 95%
“…Heterotrophic microalgae culture has proven to be able to accelerate both cell growth rate [34] and cell density [44], decreasing costs for their cultivation and harvesting. Also, glucose used as main source for heterotrophic cultivation has been gradually replaced by low-cost alternatives, such as the hydrolysed product obtained from cellulosic materials [45], glycerol [42], or wastewater from several sources [46].…”
Section: Cultivation Modesmentioning
confidence: 99%